PENGARUH PENDEKATAN DEEP LEARNING TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPAS KELAS IV di SD NEGERI 122399 JL. MAWAR PEMATANGSIANTAR - Ananda Amelia, Ananda; Rio Parsaoran Napitupulu; Esti Marlina Sirait (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the Deep Learning approach on student learning outcomes in the subject of Natural Sciences (IPAS) on the water cycle in grade IV of UPTD SD Negeri 122399 Jl. Mawar Pematangsiantar in the 2025/2026 Academic Year. The background of this study is based on low student learning outcomes, lack of student activity in the learning process, and the use of learning methods that are still teacher-centered. The Deep Learning approach is applied to create meaningful, reflective, and enjoyable learning so that students are able to understand the concept in depth. This study uses a quantitative method with a pre-experimental research type and a One Group Pretest-Posttest design. The research sample consisted of 28 grade IV students. Data collection techniques were carried out through observation, documentation, and tests. The research instruments were pretest and posttest questions that had been tested for validity and reliability. Data analysis was carried out using normality tests, N-Gain tests, and hypothesis tests. The results showed that there was an effect of the Deep Learning approach on student learning outcomes in the subject of Natural Sciences. This was evidenced by the increase in students' average scores after being given treatment and the results of hypothesis tests that showed a significant effect. Thus, the Deep Learning approach can be used as an alternative learning approach to improve elementary school students' learning outcomes. Implementing this approach helps students engage in more active discussions, express their opinions, and connect learning material to everyday life. Therefore, teachers are advised to implement student-centered learning to improve quality in elementary schools.